Powiatowa Ludowa Szkoła Rolnicza w Sędziejowicach (1924–1939) - Michalska-Gała, Magdalena; Michalski, Michał (Zeszyty Wiejskie, 2013)
The Folk Agricultural School in Sędziejowice commune was an educational facility organizing agricultural courses between 1924 and 1939, each of which lasted eleven months. The curriculum was based on the combination of typical subjects with agriculture-related classes that were additionally supplemented by practical exercises. During 15 years of operation of the school, there were 463 graduates, 393 of whom completed the whole course. Students from the area of Łaski district could obtain professional agricultural knowledge here and use it later while working in their own agricultural holdings. Theoretical and practical subjects were taught by 14 tutors. Teachers were active socially, both in the case of Sędziejowice and the Łaski district, by providing agricultural courses, among others. The school had its own agricultural holding of the acreage of 33.5 ha, the integral parts of which were an orchard and an apiary. During the interwar era, the school was the main education facility in the Łaski district and in areas surrounding it.